Characterization of Primary Human Dermal Fibroblasts to Ensure for Instance EMF Exposure Experiments under Comparable Cell Culture Condition. Issue 1 (July 2020) - Franchini, Valeria; Müller, Thomas; Haupt, Julian M.; Ostheim, Patrick; Majewski, Matthaeus; Lista, Florigio; Port, Matthias; Abend, Michael
Abstract : Abstract: HDFa (human dermal fibroblasts) are used as cellular models for EMF exposure. To ensure reproducible in vitro experiments, comparable proliferation and differentiation cell conditions must exist, and different donors, passage numbers, culture time, and growth media must be considered. In this study, the authors cultured fibroblasts in DMEM or 106 medium. Growth curves, vitality, morphology, and gene expression of genes coding for proliferation (PCNA, CDKN2A, CDKN1A, SFN), differentiation (PDGFRA, TGM2, ACTA2, PDPN, NTN1, MGP, PPP1R14), and SFN target genes (TP63, MMP1, MMP3) were examined in both media and passage numbers 3–4, 5-6 and >6. At passages 3–4, proliferating cells can be observed in both media. While cells cultured in DMEM proliferate over the passages, from passage 5, cells in 106 medium persisted around the seeded number. TGM2 down-regulation over all passages in both media and cells morphology suggest papillary-type fibroblasts. Downregulation of SFN (negative regulator of mitotic translation and cell differentiation) coincided with proliferating fibroblasts over all examined conditions. Downstream SFN target genes in proliferating cells appeared upregulated (TP63) and downregulated (MMP1/MMP3), suggestive for a status characterized by increased stemnesses (upregulated TP63) and wound healing capacity (downregulated MMP1, MMP3). Resting cells (SFN control values) were associated with control values of TP63 and MMP1/MMP3 expression, suggesting a reduced stemness and wound healing capacity. In conclusion, a set of markers related to proliferation (SFN), differentiation (TGM2), stemnesses (TP63), and wound healing (MMP1/MMP3) allow a culture characterization so that cells under two different conditions can be exposed, thus enabling reproducible EMF experiments or experiments with other exposures.